MICRONEEDLES ASSISTED ENHANCEMENT OF TRANSDERMAL DELIVERY OF CURCUMIN THROUGH ORGANOGEL FORMULATION (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
Curcumin is a natural compound found in turmeric and has been shown to have anti-inflammatory and antioxidant properties. Topical delivery of curcumin through an organic emulsion-based gel can effectively target inflammation at specific sites on the body. The current study aims to formulate Pluronic based organogel of curcumin, whose absorption is further assisted by microneedles technology. Nine organogel formulations were prepared and optimized by 32 full factorization model to fix the ratio of lecithin[A] and Pluronic[B] concentration in order to get optimum drug release after 2 hours (Q2) and maximum release of drug after 8 hours (Q8). The in-vitro study through the Franz diffusion cell indicated a significant impact of Pluronic F-127 concentration on the release of drug. As increased concentration of Pluronic increased the viscosity of formulations which ultimately retarded the release of drug. Based on Design of Experiment (DoE) study, optimized batch containing 6.5% lecithin and 20.6% Pluronic was further studied for microneedle assisted ex-vivo skin permeation through rat skin. Permeation without microneedle poration was around 70.26% after 8 hours, which was significantly increased (around 25%) after microneedle treatment of the skin. The results indicated promising application microneedle assisted skin permeation as a non-invasive and controlled delivery of curcumin through the transdermal route. Further, in-vivo studies are recommended to further establish this promising concept, targeting a variety of inflammatory conditions, including arthritis, psoriasis, and eczema, etc., through non-invasive transdermal drug delivery systems.